METODE PENAFSIRAN AL-QUR'AN - Yusuf, Muhammad Yunan (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
The Qur'an was revealed in Arabic. In understanding the Qur'an, for the people who use the Arabic language and the people who do not use Arabic language needs specific competence. Without the competence, people will not be able to capture the content and message of the Qur'an correctly. The specific competence is interpretation/tafsir. Tafsir has thariqah at-tafsir, a method or a way of interpreting the Qur'an. Errors in understanding Qur'an will also cause errors in delivering the teaching Qur'an. The interpretations’ clerics explain that in interpreting the Qur'an, there are four methods: 1) tahlili method, 2) ijmali method, 3) comparison method and 4) thematic method.